COGNITIVE AND CULTURAL DIMENSIONS OF RIDDLE TYPOLOGY: ENGLISH AND KARAKALPAK PERSPECTIVES - Sagatova, Z. (SCIENCE and SOCIETY, 2025)
The present article is devoted to comparative typological analysis of English and Karakalpak puzzles according their function, structure and form. The study of puzzles not only demonstrates the richness of human linguistic and creative abilities but also offers profound insights into the cultural identities and experiences of different peoples.
Keywords: riddles; puzzles; typological analysis; form; function; oral traditions; cultural metaphore; structure